2020
DOI: 10.1101/2020.11.27.401125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Dutch Microbiome Project defines factors that shape the healthy gut microbiome

Abstract: The gut microbiome is associated with diverse diseases, but the universal signature of an (un)healthy microbiome remains elusive and there is a need to understand how genetics, exposome, lifestyle and diet shape the microbiome in health and disease. To fill this gap, we profiled bacterial composition, function, antibiotic resistance and virulence factors in the gut microbiomes of 8,208 Dutch individuals from a three-generational cohort comprising 2,756 families. We then correlated this to 241 host and environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 66 publications
(88 reference statements)
9
53
2
Order By: Relevance
“…Another study found an increase in family Desulfovibrionaceae in individuals with high alcohol consumption 48 , and family Desulfovibrionaceae, genus Desulfovibrio and other related taxa were also associated with increased consumption of alcohol in our DMP cohort 16 , supporting a pleiotropic effect of this locus on both microbiome and alcohol intake. These studies, together with our findings, suggest that gut microbiota could indirectly influence an individual's food preferences by mediating the downstream effect of consumption of different products.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Another study found an increase in family Desulfovibrionaceae in individuals with high alcohol consumption 48 , and family Desulfovibrionaceae, genus Desulfovibrio and other related taxa were also associated with increased consumption of alcohol in our DMP cohort 16 , supporting a pleiotropic effect of this locus on both microbiome and alcohol intake. These studies, together with our findings, suggest that gut microbiota could indirectly influence an individual's food preferences by mediating the downstream effect of consumption of different products.…”
Section: Discussionsupporting
confidence: 73%
“…We further investigated the effect of diet at the LCT and ABO loci, taking into account the dominant inheritance model at LCT and the dependence on secretor status at ABO. From 21 dietary factors derived from a food questionnaire, we considered those previously found to be associated (FDR < 0.05) with the microbial taxa and pathway abundances showing genome-wide association signals in these two loci (see Methods) 16 . For the genus Collinsella and pathway LACTOSECAT-PWY, no dietary factors were found at this FDR threshold, we therefore considered the same diet factors associated to B. bifidum in the analyses, given that they showed similar patterns of genetic association.…”
Section: Genetic Associations Are Not Confounded By Intrinsic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also included 1,183 pro led metagenomes from identically processed samples from age-, sex-and BMImatched healthy DMP controls ( Fig. 1) 21 . To analyze the gut microbiome in end-stage disease, 87 ESLD and 78 ESRD patient samples were collected prior to transplantation.…”
Section: Resultsmentioning
confidence: 99%